Aplikasi agens hayati kombinasi liquid smoke untuk pengendalian penyakit busuk buah kakao - Sianturi, Lira Sonia; Sitepu, Denny Rahmad; Surapati, Faradise Puan (Jurnal Teknologi Cerdas, 2024)
The low production of cocoa plants is caused by attacks from the pathogen Phytophthora palmivora, which leads to cocoa pod rot. This can be controlled using biological agents (rhizobacteria, and Trichoderma sp.) combined with liquid smoke, which aids in disease management. The research aimed to control P. palmivora using these biological agents with different liquid smoke concentrations. A quantitative approach was employed, with in-vitro and in-vivo tests using four samples per treatment. The observed parameters included disease infection rate and disease diameter progression. The data were then tabulated and analyzed descriptively. Results consistently showed that combining biological agents with 3% liquid smoke provided the most effective control of P. palmivora, outperforming other treatments, including controls. To improve resistance to cocoa pod rot and boost production, applying this combination is recommended. Further research should be conducted to test the consistency of these results in various cocoa cultivation areas in East Kalimantan.